Changing gender gap and practice patterns in reproductive endocrinology and infertility subspecialists in the United States: a Society for Reproductive Endocrinology and Infertility report - Stadtmauer, Laurel; Sadek, Seifeldin; Richter, Kevin S; Amato, Paula; Hurst, Bradley S (Fertility and sterility, 2022)
To identify changes in current practice patterns, salaries, and satisfaction by gender and by years in practice among board-certified reproductive endocrinology and infertility (REI) subspecialists in the United States. Cross-sectional web-based survey including 37 questions conducted by the Society for Reproductive Endocrinology and Infertility. Not applicable. None. None. The primary outcome measures were total compensation and practice patterns compared by gender and the type of practice. The secondary outcomes included demographics, the number of in vitro fertilization cycles, surgeries performed, and the morale of survey respondents. There were 370 respondents (48.4% women and 51.4% men). Compared with a similar survey conducted 6 years earlier, a 27% increase in the number of female respondents was observed in this survey. There was a marginally significant trend toward lower compensation for female than male REI subspecialists (17% lower, $472,807 vs. $571,969). The gap was seen for responders with ≥10 years' experience, which is also when there was the largest gap between private and academic practice (mean $820,997 vs, $391,600). Most (77%) felt positively about the current state of the reproductive endocrinology field, and >90% would choose the subspecialty again. There has been a substantial increase in the number of recent female REI subspecialists showing less disparity in compensation, and the gap appears to be closing. There is an increasing gap in compensation between private and academic practices with ≥5 years of experience. Reproductive endocrinology and infertility remains a high morale specialty.